Outcome of large- and small-for-gestational-age babies born to mothers with pre-pregnancy and gestational diabetes mellitus versus without diabetes mellitus - K E, Elizabeth; Ashwin, David Ashok; S, Sobhakumar; T L, Sujatha (Indian Journal of Child Health, 2018)
Introduction: The prevalence of diabetes mellitus (DM) is on the increase among general population and prenatal mothers. The feto-maternal outcome of mothers with DM varies with the type of DM, pre-pregnancy or gestational (PPDM and GDM), and glycemic control. Objective: The objective of this study is to assess the outcome of small- and large-for gestational-age (SGA and LGA) babies born to a cohort of mothers with PPDM and GDM and without DM. Materials and Methods: This cohort study was conducted in a tertiary care teaching hospital. A total of 480 mothers and their newborn babies were enrolled before 6 weeks of gestation and were categorized into PPDM, GDM, and no DM subgroups. Mothers were managed as per the standard protocols. Parameters observed were optimum/suboptimum glycemic control, neonatal weight, GA, morbidity, mortality, and neonatal intensive care unit (NICU) stay. Results: A total of 19.5% mothers had PPDM, including 70 mothers already diagnosed as DM, while 39% had GDM and 41.5% had no DM. The detection rate of PPDM was 5.6% and GDM was 17.5%. Majority of the mothers with PPDM and GDM required insulin and two-third had optimum glycemic control. Good glycemic control resulted in more appropriate-for-GA babies. SGA babies were more in PPDM group (54%), followed by GDM (26%) and non-DM (21%) subgroups, while LGA babies were less in these groups, i.e., 9.6%, 5.9%, and 0.5%, respectively. The following observations were statistically significant among PPDM compared to GDM: SGA (relative risk [RR] 2.1, 95% confidence interval [CI] 2.9–3.6), congenital anomalies (RR 3.3, 95% CI 5.1–8.8), and neonatal mortality (RR 4, 95% CI 2.1–3.2). Prematurity and NICU admission with longer stay were also more in PPDM. Macrosomia and birth injury were more in GDM. Hypoglycemia, longer NICU stay, and macrosomia were more with poor glycemic control. Conclusions: A change in profile with more SGA and less LGA babies was noted in this study. Differential short-term outcomes were noted, based on the onset of DM and glycemic control. Pre-pregnancy/early first-trimester screen followed by second and third trimester screens and optimum glycemic control, throughout pregnancy, is recommended.